Kontribusi Pesantren Salaf dalam Memperkuat Islam Ahl Al-Sunnah Wa Al-Jama’ah (Studi Terhadap Kajian Dan Penggunaan Hadis pada Forum Bahtsul Masa’il Pondok Pesantren (FBMPP) Pare Kediri) - Khamim (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2015)
Three pesantren salaf joining in Bahtsul Masaâ€™il Forum of Pesantren Pare, those are Pesantren Fathul â€˜UlumÂ Kwagean, Darussalam Sumbersari and Mahir ar-Riyadh Ringinagung, are engaged in composing â€œMeluruskanÂ Kesalahan Buku Putih Kiai NUâ€as a review for â€œBuku Putih Kiai NUâ€ by Afrakhi, a book that has arisen unrestÂ and slander among the Muslim. In this book, hadith is used and comprehended employing method and approachÂ of understanding hadith. This study is examining the contribution of pesantren salaf in strengthening IslamÂ ahl al-sunnah wa a al jamaâ€™ah related to the review and usage of hadith, as well as the underlying background.Â This qualitative field research uses phenomenological approach. The results show that the contribution ofÂ pesantren salaf in strengthening Islam ahl al-sunnah wa a al-jamaâ€™ah are providing hadith that is comprehendedÂ as the source of jurisprudence or, related to a problem, examining, reviewing, and synthesizing the hadith withÂ other hadith or relating it with Al-Qurâ€™an. Such contribution was underlied by a view that hadith constitutes aÂ source of Islamic jurisprudence, by societal demand and the appeal of religious institution to put hadith at theÂ results of Bahthul Masaâ€™il decision, and by the necessity of hadith contextualization as well.